(untitled) (Bodhi Path, 2025)
Siddaṭṭha Gautama, heir of King Suddhodhan and Queen Māhāmāyā of Kapilvaṭṭhu kingdom achieved Perfect Enlightenment, Bodhi after accomplishing all the ten perfections beneath the Peepal (Ficus Religiosa) tree eminent as “Bodhi Tree” at Urevella, presently known as Bodhagaya. The our Buddha meditated for several eons to accomplish all the ten perfections from the time of Dipāṅkar Buddha, the first Buddha in the chronology of Buddhas. At the time of Dipānkar Buddha, Siddaṭṭha Gautama, our Buddha, was born as Sumegha Pandita in a wealthy and erudite family. He renounced his royal family’s luxury life, vast assets and eminence after passing away of his parents and became an ascetic thereafter. One day Dipāṅkar Buddha had to visit a city, Sumegha Pandita observed that some people of the city were busy in decorating the place in a beautiful manner to welcome him. He comes to know after enquiring a person that Dipānkar Buddha was being visited this place. Thereafter he requested to do some work in honour of Dipānkar Buddha. He was allowed to fulfil his volition. The Bodhisattva Sumegha Pandita made an aspiration at the feet of Dipānkara Buddha that he would achieved Enlightenment like Dipānkar Buddha and become a Buddha in the future. These Ten Perfections become the standard constituents of the Bodhisattva’s practice and the essentials requirements for achieving ultimate goal, The Bodhi. The practice of ten perfections is treated in broad and general terms to be accomplished by practising Vipassanā meditation. The technique of Vipassanā meditation passes directly from the time of Buddha through the chain of teachers-students tradition for a period of thousand years.